A review of the use of new technologies in physical therapy rehabilitation: possibilities and challenges with Xbox and kinect. (14th June 2019) - Gonzalez, Ivo Pedro; Garcia, Fábio Madureira; Silva, Karla Souza Caggy Costa Da; Ferreira, Fernanda Xavier; Silva, Jaqueline Ribeiro Da; Chagas, Wylena Monteiro Das
The constant search for innovations differentiates many companies. This study aims to analyse the possibilities of the new technologies in the physiotherapeutic rehabilitation process. Hypothetically the kinect as new technology associated with conventional physiotherapy rehabilitation brings positive results. Through the review study, we intend to demonstrate the possibilities of using kinect in this process, identifying what is the applicability of the use in physiotherapeutic rehabilitation as well as the possible use of multiple tools in the treatment of patients through new technologies. The proposal of this research is based on the need to increase the knowledge needed to maximise results when using a new tool. This study is based on a review study, between 2014 and 2015, in which a query was made to scientific articles selected through search of keywords in several databases. This study indicates the positivity of Kinect as a tool allied to physiotherapy treatment.